2019
DOI: 10.59665/rar3612
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Resources for Improving Resistance to the Main Diseases in Sunflower

Abstract: Genetic resources in sunflower, which could to be used as base of creating new inbred lines or as donor sources for genes controlling different characteristics in the inbred lines breeding, are made up of old or new varieties, hybrids and inbred lines, induced mutations, synthetic populations, as well as sunflower wild species. For improving sunflower resistance to the main diseases all these genetic resources can be used. In the sunflower breeding program of the National Agricultural Research & Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Meanwhile, the pathogen appeared also in temperate climate, such as France (Penaud and Perny, 1995), Hungary (Zoltan, 1995), Germany (Thines et al, 2006) and Belgium (Crepel et al, 2006). As Rîşnoveanu, et al (2019), for improving sunflower resistance to the main diseases, genetic resources can be used, as well as sunflower wild species. Rost and Thines (2011) found that Pustula tragopogonis is an illegitimate name because the oldest name of the genus level, Uredo tragopogonis (Pers.)…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the pathogen appeared also in temperate climate, such as France (Penaud and Perny, 1995), Hungary (Zoltan, 1995), Germany (Thines et al, 2006) and Belgium (Crepel et al, 2006). As Rîşnoveanu, et al (2019), for improving sunflower resistance to the main diseases, genetic resources can be used, as well as sunflower wild species. Rost and Thines (2011) found that Pustula tragopogonis is an illegitimate name because the oldest name of the genus level, Uredo tragopogonis (Pers.)…”
Section: Introductionmentioning
confidence: 99%